2021
DOI: 10.1111/ijcp.14509
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin prevents pregnancy‐induced hypertension via suppression of JAK/STAT3 signalling pathway in mice

Abstract: Pregnancy-induced hypertension (PIH) is also called gestational hypertension, which is developed in the late pregnancy. It is estimated that 7%-10% of pregnancies are affected by PIH which compromises the normal pregnancy process. 1 PIH has been considered as the major cause of perinatal and maternal mortality. 2 The pathogenic mechanisms of PIH remain unclear. One of the major hallmarks in PIH is endothelial dysfunction. Endothelial cells line the internal lumen of the vasculature and participate in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In my opinion, this is first research to comprehensively investigate the impacts of dietary flavonoid intake upon the PE risk in a Chinese population Our study found that high intake levels of dietary flavanones (naringenin) and luteolin were associated with more than 40 % reduced risks of PE, with a significant dose-response trend. This corresponds to these consequences of Duan et al [18] that studied mice with gestational hypertension exposed to 50 mg/kg of naringenin during gestation and found that naringenin could markedly attenuate the systemic inflammatory response by lessening serum levels of the pro-inflammatory cytokines IL-2, IL-6 as well as TNF-α. Qin et al [19] found that naringenin reduced endothelial dysfunction induced by high glucose concentrations among the endothelial cells.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…In my opinion, this is first research to comprehensively investigate the impacts of dietary flavonoid intake upon the PE risk in a Chinese population Our study found that high intake levels of dietary flavanones (naringenin) and luteolin were associated with more than 40 % reduced risks of PE, with a significant dose-response trend. This corresponds to these consequences of Duan et al [18] that studied mice with gestational hypertension exposed to 50 mg/kg of naringenin during gestation and found that naringenin could markedly attenuate the systemic inflammatory response by lessening serum levels of the pro-inflammatory cytokines IL-2, IL-6 as well as TNF-α. Qin et al [19] found that naringenin reduced endothelial dysfunction induced by high glucose concentrations among the endothelial cells.…”
Section: Resultssupporting
confidence: 61%
“…Qin et al [19] found that naringenin reduced endothelial dysfunction induced by high glucose concentrations among the endothelial cells. Perhaps, Naringenin's protective effect against endothelial dysfunction is partly regulated through down-regulating the apoptosis and oxygenated stress by means of Phosphorylation of Protein Kinase C βII (PKCβII)-associated caspase-3 and Nitric Oxide (NO)/Reactive Oxygen Species (ROS) pathway among endothelial cells [18][19][20] . Previous studies have indicated that hesperetin treatment can significantly lessen these expressions of Matrix Metalloproteinase (MMP) and MMP-9, while MMPs have been shown to be related to angiogenesis and metastasis [21,22] .…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the JAK2/STAT3 signaling pathway is closely related to the progress of HDP. Using inhibition of the JAK2/STAT3 signaling pathway (AG490) 36 or Naringenin 37 can reduce the secretory ability of vascular endothelium cells through inhibition activation of the JAK2/STAT3 signaling pathway, and further improve HDP. Then, in this study, we found that NANOG could regulate the expression of STAT3, inhibit JAK2/STAT3 signaling pathway, and promote trophoblast cell proliferation, migration and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the serum levels of IL-2, IL-6, and TNF-α were decreased, while IL-10 was increased. Interestingly, naringenin inhibited Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling by suppressing Src homology region 2 (SH-2) domain-containing phosphatase 1 (SHP-1) expression in vascular endothelial cells [65]. Additional protective effects of naringenin on kidney damage may stem from its capacity to regulate vascular tone by influencing enzymes responsible for metabolizing vasoactive substances and hypertensive mechanisms.…”
Section: Cardiovascular Effects Of Naringenin and Their Role On Diabe...mentioning
confidence: 99%